Ifosfamide-induced encephalopathy: the EEG with frontal intermittent delta activity, and rapid resolution with methylene blue: A case report. - Kelleher, Fergal (My University, 2020)
Background: Encephalopathy is an established side effect of the chemotherapeutic agent, ifosfamide, occurring in 10-30% of cases. The EEG commonly shows non-specific features of encephalopathy, and rarely shows frontal intermittent rhythmic delta activity (FIRDA). Case presentation: This is a case report of a 71 year old woman with pleomorphic sarcoma, who developed ifosfamide-induced encephalopathy with her second dose of ifosfamide. It shows the characteristic EEG findings that have been described previously with ifosfamide-induced encephalopathy and additionally the unusual and rare finding of FIRDA. This was followed up by a further EEG showing resolution of the encephalopathy, after administration of methylene blue, coinciding with rapid and complete resolution of her symptoms. Conclusion: The rapid resolution of the encephalopathy on the EEG after administration of methylene blue adds further evidence to its effectiveness as a treatment for the disorder.
Keywords: Encephalopathy; Frontal rhythmic intermittent delta activity FIRDA; Ifosfamide; Methylene blue; Cancer; Health